PENGARUH PENGGUNAAN MODEL TWO STAY TWO STRAY TERHADAP HASIL BELAJAR IPS SISWA DI SD - Jannah, Miftahul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aims to find out how much influence the use of Two Stay Two Stray model to the learning outcomes of IPS students of class V SDN 25 Sungai Raya ". Research method used is experimental method with Quasi Experimental Design with Design Nonequivalent Control Group Design. Subjects of the sample were VA students consisting of 32 students (experiments) and 38 students (control) VB class. The research instrument is a matter of multiple choice test with 30 questions. Based on data analysis, the average of post test experiment class result is 73,25 and average result of post test of control class 63,92. Based on the T test with significance tarithmetic 3,8274 and ttable Î± = 5%Â  equal to 1,6693, which means tarithmetic (3,8274)> ttabel (1,6693), then Ha be accepted. Thus, it can be concluded that there is an influence of the use of Two Stay Two Stray model to the learning outcomes of Social Science students of class V SDN 25 Sungai Raya. The ES calculation is 1.01 (high criterion). This means that the use of Two Stay Two Stray model gives a high influence on students' social learning outcomes in class V SDN 25 Sungai Raya. Â  Keywords : Two Stay Two Stray, Learning Outcomes Â